Genes on the menu facts for knowledge-based decisions - Pechan, Paul (Springer Berlin Heidelberg, 2005)
Only little more than a decade ago the term "genetic engineering" was hardly known outside research laboratories. Today it regularly makes headlines in the news. Supporters and opponents as well tell us that it could change our lives more than any other technological advance. This book delivers the state-of-the-art facts in order to empower the public to make knowledge-based decisions about plant biotechnology and GM crops and GM food, in particular. It discusses the hot topics of the present debate in a neutral manner and will function as a personal reference book for the interested public, for decision maker, and managers of consumer organisations. GMO issues toda: an introduction - Public perception of plant biotechnology - What is biotechnology? - History and current uses of plant biotechnology - Environmental concerns associated with GMOs - Herbicide tolerance - Virus resistance - Insect resistance - Second generation products (quality-oils, proteins, starch etc.) - Third generation products (biofactories etc.) - GMO: Intellectual property rights - Labelling issues - Monitoring and risk assessment - Ethical aspects of the GMO debate - Hoaxes, positive and negative aspects of GMOs with examples - Regulatory and legislature issues in the EU - Biotechnology activities in the CEEC - Regulatory and legislature issues in CEEC - Regulatory and legislature issues in North America - Modern biotechnology in food and agriculture: risks and benefits for the developed world - How to cope with GMOs: implementation, monitoring and enforcement - The use and implications of the precautionary principle - Intellectual property rights: consequences for world trade and social issues.